PERENCANAAN SIRKULASI RUANG PUSAT TERAPI HOLISTIK DI SAMARINDA - Nur Ramdhani, Iga; Rahayu Ningsih, Tutik; Hediananda Dwikaputri, Alvira (Jurnal Kreatif : Desain Produk Industri dan Arsitektur, 2024)
Samarinda is one of the most populous cities in East Kalimantan. Living in a densely populated urban area has a greater impact on the risk of mental health disorders. Poor mental health has an impact on physical health. One effort for health care is by conducting holistic health therapy as an alternative to healing overall health, starting from a person's physical, emotional, social, and spiritual health. The purpose of this planning is to produce a holistic therapy center building design in Samarinda with circulation planning that can facilitate building users in their activities in it. Through the analysis method by analyzing the area and building circulation. Analysis of area circulation is carried out by arranging vehicle lanes, parking and building positions. Analysis of building circulation is carried out by determining the pattern of vertical and horizontal space circulation. This planning produces a holistic therapy center in Samarinda that has a circulation space that can increase comfort and facilitate access for building users, so that this therapy center can meet the needs of urban physical and psychological health and become a place for a healthy environmental community